Economics of gastroenteropancreatic neuroendocrine tumors: a systematic review. (February 2019) - Grande, Enrique; Díaz, Ángel; López, Carlos; Munarriz, Javier; Reina, Juan-José; Vera, Ruth; Bernárdez, Beatriz; Aller, Javier; Capdevila, Jaume; Garcia-Carbonero, Rocio; Jimenez Fonseca, Paula; Trapero-Bertran, Marta
Background: Despite current interest, enthusiasm and progress in the development of therapies for gastroenteropancreatic (GEP) neuroendocrine tumors (NETs), there are substantial gaps in the published literature regarding cost-of-illness analyses, economic evaluation and budget impact analyses. Compounding the issue is that data on resource utilization and cost-effectiveness of different diagnostic and therapeutic modalities for GEP-NETs are scarce. Methods: A systematic review on the economic impact of GEP-NETs was carried out using four databases: EMBASE, PubMed, the National Health Service Economic Evaluation Database and Cochrane review . Fully published articles from January 2000 to May 2017, in English and Spanish, were included. All articles that satisfied the inclusion criteria were included in the systematic review; summary descriptive statistics were used to describe the methodological characteristics. Results: The 14 studies selected included cost-of-illness analyses ( n = 4), economic evaluations ( n = 7) and budget impact analyses ( n = 3). Almost all studies were performed in the United States. Healthcare costs for patients with NETs included medication, outpatient visits, hospitalizations, and check-ups/tests. Reducing adverse events is an area where cost savings could be achieved; however, there was not enough evidence on the cost impact of adverse events. Conclusion: There is a lack of data related to resource utilization in the field of GEP-NETs. Therefore, cost-effectiveness and budget impact studies of existing and emerging treatments are urgently needed to help the decision-making process for patients with NETs.